The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1477-7819-12-207
|View full text |Cite
|
Sign up to set email alerts
|

Norcantharidin induces growth inhibition and apoptosis of glioma cells by blocking the Raf/MEK/ERK pathway

Abstract: BackgroundMalignant gliomas represent the most common primary brain tumors. The prognosis of patients with malignant gliomas is poor in spite of current intensive therapy and novel therapeutic modalities are needed. Here we report that norcantharidin is effective in growth inhibition of glioma cell lines in vitro.MethodsGlioma cell lines (U87 and C6) were treated with norcantharidin. The effects of norcantharidin on the proliferation and apoptosis of glioma cells were measured by 3-[4,5-dimethylthiazol-2-thiaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
0
20
1
Order By: Relevance
“…In our study, while no significant change of Bax was noted, previous studies have shown that increased expression of Bax was noted in the NCTD‐induced HepG2 apoptosis . However, NCTD–treated glioma cells had nearly no effect on expression of the Bcl‐xL or Bax . These results pointed out that the expression of Bcl‐2 family in NCTD‐induced apoptosis is cell‐specific.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In our study, while no significant change of Bax was noted, previous studies have shown that increased expression of Bax was noted in the NCTD‐induced HepG2 apoptosis . However, NCTD–treated glioma cells had nearly no effect on expression of the Bcl‐xL or Bax . These results pointed out that the expression of Bcl‐2 family in NCTD‐induced apoptosis is cell‐specific.…”
Section: Discussioncontrasting
confidence: 51%
“…NCTD is the demethylated analog of cantharidin, which is isolated from blister beetles ( Mylabris phalerata Pall). Currently, studies in vitro and in vivo pointed out that NCTD was cytotoxic to several tumor cells . Previous study shown that mitochondrial pathways is critical in NCTD induced apoptosis in the HeLa human cervical cancer cell lines .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that NCTD may exert its functions by regulating MAPKs signaling pathways in other cancer cells 10,12,14 . Here, we found that FAM46C expression was enhanced by NCTD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gliomas represent the most aggressive and the most common primary central nervous system tumours and are related with very poor survival . Surgical resection with temozolomide‐based chemotherapy and radiotherapy has become the norm of treatment in gliomas . In recent years is a growing interest in medicinal plants due to their bioactive substances.…”
Section: Introductionmentioning
confidence: 99%